On-farm conservation for traditional mango varieties - Rajan, Shailendra; Yadav, Ashish (Indian Horticulture, 2021)
Mango varieties are abundant in India, as they grow in tropical and sub-tropical climates and come in over a thousand varieties. Traditional mango varieties have a wide range of unique flavours, nutritional and medicinal properties. A large number of old mango varieties are being conserved by custodian farmers. Their efforts will demonstrate on-farm conservation of mango diversity. Non-commercial mango varieties grown by farmers are critical for conservation. Traditional varieties help farmers’ livelihoods in areas where commercial varieties are scarce. Mango festivals can play an important role in demonstrating diversity.